Pesan Kreatif Iklan Televisi Dalam Bulan Ramadan: Analisis Semiotika Iklan Bahagianya adalah Bahagiaku - Andrianto, Novan (Jurnal Studi Komunikasi, 2018)
The commercial advertising is one the most famous and the most discussed promotion tool because of its scope. One of the products using Television Commercial, as the promotion tool in Ramadan, is Ramayana Department Store. Before and During the Ramadan, most Moslems have their activities in Ramadan with themselves, their society, their colleagues and their beloved families. In Ramayana Ramadan Commercial "Their Happiness is My Happiness" ("Bahagianya Adalah Bahagiaku"), aired in the television, aimed: (1) to know the family relation to the meaning of Ramayana Ramadan Commercial "Their Happiness is My Happiness" ("Bahagianya Adalah Bahagiaku") for Indonesian Moslems' habit during Ramadan. (2) To discover the creative message in Ramayana Ramadan Commercial "Their Happiness is My Happiness". For this commercial analysis, the writer applied Content Analysis Approach and Communication Semiotics approach. Based on the analysis in each part of the commercial, the writer found the process of the delivered message by Ramayana Ramadan Commercial. The message is related to the unstoppable habits of Indonesian Moslem, from the past until now, about the roles of Moslems for having fast at the holy month of Ramadan.